Social Emotional Ability Children with Special Needs in Novel Sakura's Secret: A Piece of The Secret about Which Can Never be Perfect - Mustakimah (International Proceedings of Nusantara Raya, 2022)
By nature, every human being is born in a state of goodness from all sides. Good or bad their physical condition is not a barrier for them to become good people with all their potential. Having a defect in their body is not something they ask for and even if they can't deny it because it has become a written lifeline. Sakura Celllogienah is one example of a girl who with various limitations experienced even though not from birth can make so many learning achievements beyond those who are "normal children" and not only that, she also has to go through so many life tests to be able to stay afloat. on a line that led him to become a superior person. The research method used is a literature study. Documentation technique is the method used in collecting data, namely by reading thoroughly, understanding and examining the contents of the novel, and then identifying the correlation with the existing theory so that valid and detailed data results will be obtained. The results of this research can be stated that the social emotional value is implied in the novel Sakura's Secret in the form of the importance of self confidence, harmony, tolerance, help, and empathy when interacting in a society or group by putting aside the ego of each group member so as to form a harmonious and superior society. This is related to what was expressed by JJ Rouseau and John Locke about the basic concept of the philosophy of the child that children are not born with sin, but they assume that using the rationalist concept that children, regardless of their physical condition, are unique individuals with all their potential as a regeneration of a more dignified future.